Hall of Fame Article: Minimally Invasive and Regenerative Therapeutics (Adv. Mater. 1/2019). Issue 1 (3rd January 2019) - Ashammakhi, Nureddin; Ahadian, Samad; Darabi, Mohammad Ali; El Tahchi, Mario; Lee, Junmin; Suthiwanich, Kasinan; Sheikhi, Amir; Dokmeci, Mehmet R.; Oklu, Rahmi; Khademhosseini, Ali
Abstract : Advances in microscale fabrication techniques have enabled novel therapeutics to be developed (cells, biomaterials, biomolecules or their combinations), delivered to the body via minimally invasive procedures. These therapeutics can be used to help regenerate various tissues, with lower risk of complications, reduced cost, and improved outcome, and are reviewed by Nureddin Ashammakhi, Ali Khademhosseini, and co‐workers in article number1804041 .